2017
DOI: 10.1108/jopp-03-01-2003-b003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of purchasing’s organizational roles and responsibilities in the public and private sector

Abstract: This research focuses on a comparison of public and private sector supply organizations in terms of organizational structure, supply chain responsibilities, the chief purchasing officer (CPO) and reporting line, teaming and involvement in major organizational activities. A unique opportunity to identify similarities and differences was presented in 2000 when the National Institute of Governmental Purchasing Research (NIGP) and Florida Atlantic University replicated in the public sector a study that the Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 13 publications
1
47
0
2
Order By: Relevance
“…Laios and Xideas (1994a) showed in an empirical study that purchasing is more formalized in public institutions than in private companies, but that no distinct tendency towards centralization in purchasing could be identified. In contrast, Johnson et al (2003) found out that public institutions used a higher degree of centralization in their purchasing activities.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Laios and Xideas (1994a) showed in an empirical study that purchasing is more formalized in public institutions than in private companies, but that no distinct tendency towards centralization in purchasing could be identified. In contrast, Johnson et al (2003) found out that public institutions used a higher degree of centralization in their purchasing activities.…”
Section: Literature Reviewmentioning
confidence: 89%
“…A comparison of the purchasing organization of public and private institutions can be found in Laios and Xideas (1994a) and Johnson et al (2003). Laios and Xideas (1994a) showed in an empirical study that purchasing is more formalized in public institutions than in private companies, but that no distinct tendency towards centralization in purchasing could be identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies underlined four traditional procurement principles governing public spending which are not applicable to corporate sector e.g. degree of involvement of managers in organizational activities which is more in enterprises than is prevalent in public sector, procurement decisions in corporate are on multiple factors like strategic partnership avenues, shared vision, total cost of ownership etc., while public sector must ensure level playing field for all vendors; and non monetary factors such as equity, competition, transparency limit the discretion of public procurement officials, thus inhibiting their abilities to operate at strategic levels [21,27,43]. The public procurement managers are also guided by government rules that may strive to promote a particular sector (like Small Scale Industries etc.)…”
Section: E-procurement In Public Sectormentioning
confidence: 99%
“…Moreover, there are cross-sectoral differences even in everyday IT Outsourcing in the Public Sector routines. Examination of just one isolated business process (purchasing) shows notable differences in reporting, level of centralization, and distribution of responsibilities (Johnson et al 2003). …”
Section: The Distinctive Nature Of Public Organizations Compared To Pmentioning
confidence: 99%
“…At the same time, public organizations notably share the tendency to collaborate, which may be to their advantage in many situations (e.g., Fedorowicz et al 2007;Linden 2002). While a shortage of resources increases the competition pressures in the private sector, public agencies react with increased interorganizational collaboration to reduce costs and share scarce resources (Johnson et al 2003). The noncompetitive nature of the public sector allows for forms of collaboration that are hardly possible in the business world.…”
Section: The Distinctive Nature Of Public Organizations Compared To Pmentioning
confidence: 99%